2019
DOI: 10.5194/isprs-archives-xlii-4-w14-119-2019
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science for Water Quality Monitoring Applying Foss

Abstract: <p><strong>Abstract.</strong> Citizen science is an efficient tool for data collection for scientific projects. In the framework of SIMILE Interreg Italy-Switzerland project, the citizen’s contribution to monitor the quality of lakes water has been envisaged. In the initial phase of this research, state of art of citizen science and water quality monitoring was investigated. The analysis of past and current projects, governed by different organizations and communities, pointed out a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As for the mobile application, a detailed analysis of similar tools is described in a paper from Jovanovic et al (2019). The authors presented six different applications used for water quality monitoring with a citizen science approach.…”
Section: Existing Tools For the Collection And Management Of Citizen Science Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As for the mobile application, a detailed analysis of similar tools is described in a paper from Jovanovic et al (2019). The authors presented six different applications used for water quality monitoring with a citizen science approach.…”
Section: Existing Tools For the Collection And Management Of Citizen Science Datamentioning
confidence: 99%
“…Even though most applications are free, none of them is open source. For this reason, a new mobile application has been designed according to the following criteria: it should provide user support, it has to be user-friendly, able to work offline, free, and open source (Jovanovic et al, 2019).…”
Section: Existing Tools For the Collection And Management Of Citizen Science Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The current state of the art in this field has been explored in order to find any existing solution that could satisfy SIMILE project requirements regarding citizen science. Such investigation has been conducted taking into account both applications specifically related to lake and water quality assessment (Jovanovic et al, 2019) and products generically built for data collection. Figure 1.…”
Section: Mobile Applications For Water Quality Monitoringmentioning
confidence: 99%
“…Three of the applications presented so far are free, while HydroColor has a cost of 3.5 €, all four are not open source. A more detailed review of these and other mobile applications for water quality monitoring can be found in Jovanovic et al (2019). In addition to applications specifically devoted to water quality monitoring, also applications designed for generic infield data collection have been explored.…”
Section: Mobile Applications For Water Quality Monitoringmentioning
confidence: 99%